2020
DOI: 10.3390/biology9060119
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Supplementation with Omega-6 LC-PUFA-Rich Microalgae Regulates Mucosal Immune Response and Promotes Microbial Diversity in the Zebrafish Gut

Abstract: The effect of dietary omega-6 long-chain polyunsaturated fatty acid (LC-PUFA) on host microbiome and gut associated immune function in fish is unexplored. The effect of dietary supplementation with the omega-6 LC-PUFA-rich microalga Lobosphaera incisa wild type (WT) and its delta-5 desaturase mutant (MUT), rich in arachidonic-acid and dihomo-gamma-linolenic acid (DGLA), respectively, on intestinal gene expression and microbial diversity was analyzed in zebrafish. For 1 month, fish were fed diets supplemented w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 69 publications
(83 reference statements)
4
25
0
Order By: Relevance
“…Here, we demonstrated that DGLA administration in several forms modulated the immune response in RAW264.7 macrophages. While this work was confined to a cell model, the results further support the anti-inflammatory and immunomodulatory potential of the L. incisa -derived DGLA, previously demonstrated in zebrafish feeding trials [ 23 , 63 ]. Additional studies are required to translate these findings to the use of DGLA as feed and health-promoting food supplements for conditions and pathologies that are caused by imbalance in the immune system.…”
Section: Discussionsupporting
confidence: 82%
“…Here, we demonstrated that DGLA administration in several forms modulated the immune response in RAW264.7 macrophages. While this work was confined to a cell model, the results further support the anti-inflammatory and immunomodulatory potential of the L. incisa -derived DGLA, previously demonstrated in zebrafish feeding trials [ 23 , 63 ]. Additional studies are required to translate these findings to the use of DGLA as feed and health-promoting food supplements for conditions and pathologies that are caused by imbalance in the immune system.…”
Section: Discussionsupporting
confidence: 82%
“…22 In a zebrafish study, it was also found that dietary supplementation of n-6 LC-PUFA-rich microalga resulted in elevated expression of anti-inflammatory cytokine interleukin 10 (il-10). 184 In addition, an in vitro study with head kidney leukocytes isolated from Atlantic cod revealed that a high level of ARA + EPA upregulated the gene expression of il-10 and downregulated that of the proinflammatory cytokine il-1β (Table 4). 185 However, in Japanese flounder, a concurrent increase in ARA level and inflammation symptom was observed after hemorrhagic septicemia virus infection, 186 as similarly observed in some mammal studies.…”
Section: Functions In Disease Resistance Immunity and Inflammationmentioning
confidence: 99%
“…207 However, on the opposite, in zebrafish gut, dietary supplementation of n-6 LC-PUFA-rich microalga led to higher diversity indices for microbial communities. 184 Another study with winter flounder (Pseudopleuronectes americanus)…”
Section: Effects Of Dietary Ara On Microbiotamentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the tendency of more homogeneous data (less values of variance) and medium values of diversity index between the anterior and posterior sections have been observed when the fish are fed with the FH diet. Reference 41 concluded that changes in diversity are due to an adaptation of the microbiota to digest and assimilate the ingredients added, such as cell walls, polysaccharides and lipids, which affect or modify colonization by minority groups. Avoiding loss of diversity is considered as a positive aspect that protects intestinal mucose and gives protection against diseases 42 .…”
Section: Discussionmentioning
confidence: 99%